Naive independent directors, corporate governance and firm performance - Chen, Gaocai; Chen, Xiangyu; Wan, Peng (Frontiers in Psychology, 2022)
This paper mainly explores the effect of naive independent directors on firm performance. Using hand-collected data on Chinese listed companies, this study finds that the proportion of naive independent directors is positively associated with firm performance, and an increased proportion of naive independent directors reduce the probability of tunneling of controlling shareholders and financial distress. The findings are robust after using alternative explanatory variables and retro-causality tests. Furthermore, the relation between naive independent directors and firm performance mainly existed in firms with lower shareholdings of the largest shareholder and firms with lower financial leverage. Moreover, this paper finds that firm size, corporate ownership type, and equity balance degree are important factors affecting the appointment of naive independent directors. This paper offers further empirical evidence to the existing research related to naive independent directors and provides an effective way to improve corporate board governance.